General practitioners’ attitudes and motivation to supervise medical students in clinical placements: a questionnaire study from Norway - Julie Solberg Knutsen; Gunnar Tschudi Bondevik; Steinar Hunskaar (Scandinavian Journal of Primary Health Care)
Background General practitioners (GPs) who supervise medical students during clinical placements are valuable resources for medical universities. However, several countries struggle with recruiting supervisors. More knowledge about GPs’ attitudes and factors that motivate them to be supervisors, is essential for developing targeted recruitment strategies and effective follow-up by universities.Objective We aimed to investigate GPs’ attitudes to and motivation for supervising medical students in clinical placements.Methods A web-based questionnaire was sent to all GPs in Norway in February 2022. Both active supervisors’ and non-supervisors’ responses were collected. Attitudes were reported as scores on a five-point Likert scale in response to 21 statements, while motivation was reported by highlighting the most important motivational factors among 15 items. Descriptive statistics were used to rank the statements and motivation factors. Independent sample t-test and ANOVA were used to analyse differences in mean scores across subgroups.Results We received 1466 responses (29%), of whom 498 (34%) were active supervisors. Results revealed positive attitudes towards supervising medical students in clinical placements, even among non-supervisors. Statements about the supervisor role and its importance regarding recruitment, professional stimulation and clinical teaching competence, were scored high. Many agreed that supervising students increased their workload. ‘Recruitment contribution’ was the most selected motivation item.Conclusion Recruitment contribution, professional development, workday variation and the feeling of fulfilment contribute to GPs’ motivation to supervise. The results indicate a promising future for recruiting clinical supervisors.